Mechanical, thermal, and microstructural properties of polypropylene/polyamide-6/styrene-ethylene-butadiene-styrene polymer alloys - TAŞDEMİR, MÜNİR (JOHN WILEY & SONS INC, 2003)
Interfacial agents as compatibilizers have recently been introduced into polymer blends to improve the microstructure and mechanical properties of thermoplastics. In this way, it is possible to prepare a mixture of polymeric materials that can have superior mechanical properties over a wide temperature range. In this study, an incompatible blend of polypropylene (PP) and polyamide-6 (PA(6)) were made compatible by the addition of 10% styrene-ethylene-butadiene-styrene copolymer (SEBS). The mixing operation was conducted by using a twin-screw extruder. The morphology and the compatibility of the mixtures were examined by SEM and DSC techniques. Furthermore, the elastic modulus, tensile and yield strengths, percentage elongation, hardness, melt flow index, Izod impact resistance, heat deflection temperature (HDT), and Vicat softening point values of polymer alloys of various ratios were determined. It was found that the addition of SEBS to the structures decreased the tensile strength, yield strength, elastic modulus, and hardness, whereas it increased the Izod impact strength and percentage elongation values. (C) 2003 Wiley Periodicals, Inc.
Keywords: polymer alloys; compatibilization; mixture; extrusion; polypropylene (PP); BLOCK-COPOLYMERS; BLENDS; COMPATIBILIZATION